Islamic Finance Development in Africa - Adam, Muniem; Napitupulu, Rodame Monitorir (SMART Insight, 2025)
This study provides a quantitative analysis of the literature on Islamic finance in Africa from 1992 to 2024, drawing on English, French, Turkish and Russian language articles indexed in Scopus database. Employing a bibliometric methodology alongside content analysis, this study outlines the development and structure of the field, examining aspects such as co-authorship, co-citation, and bibliographic coupling. Finding The international journal of Islam as the highest-ranking journal in Islamic finance in Africa, Hasan, M. Kabir as the most influential in co-authorship, and Islamic finance as the dominant keyword in the bibliometric analysis. The primary objective of this research is to address the lack of prior bibliometric analysis concerning Islamic finance within the context of Africa. Consequently, this research will serve as an inaugural paper conducting a bibliometric review on this particular topic. There are 4 main topics covered: (1) Overview of Islamic finance in Africa; (2) Islamic finance in developing countries; (3) Development of Islamic finance in Africa; (4) Performance of Islamic banking and finance during crises.